2023
DOI: 10.1177/0271678x231153741
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cerebrovascular resistance across the adult lifespan: A multimodality approach

Abstract: Cerebral blood flow (CBF) decreases across the adult lifespan; however, more studies are needed to understand the underlying mechanisms. This study measured CBF and cerebrovascular resistance (CVR) using a multimodality approach in 185 healthy adults (21–80 years). Color-coded duplex ultrasonography and phase-contrast MRI were used to measure CBF, CBF velocity, and vessel diameters of the internal carotid (ICA) and vertebral arteries (VA). MRI arterial spin labeling was used to measure brain perfusion. Transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 63 publications
(175 reference statements)
3
11
1
Order By: Relevance
“…The scatter plot of the CBF ASL /CBF PC ratio with respect to mean flow velocity. males, 6,7,11,12,21 while other studies have found no sex-related differences. 22,23 Using the same cohort, the findings in this study also exhibited heterogeneity.…”
Section: F I G U R Ementioning
confidence: 60%
See 2 more Smart Citations
“…The scatter plot of the CBF ASL /CBF PC ratio with respect to mean flow velocity. males, 6,7,11,12,21 while other studies have found no sex-related differences. 22,23 Using the same cohort, the findings in this study also exhibited heterogeneity.…”
Section: F I G U R Ementioning
confidence: 60%
“…Understanding the differences or consistency between these modalities in CBF quantification is essential for interpreting data across different studies. However, one aspect often overlooked in these earlier comparisons is the inclusion of subjects across a wide age range, which can contribute to increased intersubject variability 6–8 . It is crucial to acknowledge that age plays a significant role in cerebral physiology, and flow impedance starts to increase after the age of 40 years 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…difficult to directly compare, the global CBF values in untrained post-PHV males were similar to middle-aged males in a recent study that quantified global CBF in a similar manner (Tomoto et al, 2023).…”
mentioning
confidence: 50%
“…181,183,214 Under normal conditions, CBF gradually declines with increasing age in both men and women. 189,215 This decline can be accelerated in the presence of hypertension 26,[216][217][218] or conditions such as heart failure. 160 Based primarily on temporal relationships, many studies have suggested that reductions in CBF begin before the onset of cognitive decline but are accelerated in the presence of hypertension (Figure 1).…”
Section: Cerebral Blood Flowmentioning
confidence: 99%